2013
DOI: 10.1590/s1414-462x2013000300013
|View full text |Cite
|
Sign up to set email alerts
|

Inquérito domiciliar de prevalência de tracoma em crianças do Distrito Federal, Brasil, julho/2010

Abstract: Realizamos um estudo de corte transversal na Vila Estrutural (DF), utilizando amostragem por conglomerados. Os objetivos do estudo foram estimar a prevalência de tracoma em crianças de um a nove anos, descrever o perfil sociodemográfico dos casos e identificar possíveis fatores de risco associados à doença. A medida de associação foi razão de prevalência estimada pela odds ratio e o intervalo de confiança 95% (IC95%). Foram amostradas 766 crianças de 1 a 9 anos e encontrada prevalência de tracoma ativo de 12,5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
0
2
0
7
Order By: Relevance
“…Comparatively, Koizumi et al (14) , in a study carried out in São Paulo (SP), demonstrated a prevalence of 2.2% in this city, while Caninéo et al (14) , in a study carried out in Embu das Artes -SP, found a rate of 3.1%. On the other hand, a household survey carried out with children in the community of Vila Estrutural, a former invasion area in the Brazilian Federal District and under precarious conditions of sanitation, demonstrated a prevalence of 12.5% (15) , wheras in the studies of Lucena et al (16) in Porteira (CE), a rate of 26.2% was observed. Lopes et al (17) found cases of trachoma in all Brazilian States, but reported an average prevalence of 6.1% in Santa Catarina, 4.6% in Rio Grande do Sul and 4.5% in Roraima.…”
Section: Resultsmentioning
confidence: 95%
“…Comparatively, Koizumi et al (14) , in a study carried out in São Paulo (SP), demonstrated a prevalence of 2.2% in this city, while Caninéo et al (14) , in a study carried out in Embu das Artes -SP, found a rate of 3.1%. On the other hand, a household survey carried out with children in the community of Vila Estrutural, a former invasion area in the Brazilian Federal District and under precarious conditions of sanitation, demonstrated a prevalence of 12.5% (15) , wheras in the studies of Lucena et al (16) in Porteira (CE), a rate of 26.2% was observed. Lopes et al (17) found cases of trachoma in all Brazilian States, but reported an average prevalence of 6.1% in Santa Catarina, 4.6% in Rio Grande do Sul and 4.5% in Roraima.…”
Section: Resultsmentioning
confidence: 95%
“…Embora bastante prevalente em nosso meio (Silva, 2014;Jesus et al, 2013;Lopes et al, 2013;Lucena;Cavalcanti, 2010;Lopes, 2008;Paula;Medina;2002), o…”
Section: Resultsunclassified
“…A face interna das pálpebras e a esclera são recobertas por uma membrana fina e transparente chamada conjuntiva (Fig.1B) (JESUS et al, 2013;LOPES et al, 2013;DANTAS, 2013;MACHARELLI et al, 2013;CANINÉO et al, 2012;SCHELLINI et al, 2010;FERRAZ et al, 2010;LUCENA;CAVALCANTI et al, 2010 ;LOPES, 2008;ALMEIDA, 2007;KOIZUMI et al, 2005 De acordo com Thylefors et al (1987) o tracoma apresenta cinco formas clássicas (Fig.3) Certamente alcançar este objetivo seria de grande importância no combate a esta bactéria. Foram considerados todos os trabalhos publicados no período.…”
unclassified
“…Federal, e a prevalência de tracoma ativo encontrada foi de 12,5% 24 . Uma possível explicação disto pode ser devido a efeitos da pobreza sobre os cuidados de saúde, falta de higiene, alta chance de objetos/utensílios de compartilhamento, o estado de imunidade e falta de informação 20 .…”
Section: Discussionunclassified
“…Em se tratando aos hábitos de limpeza de mãos e rosto, quase todos os casos encontrados afirmaram realizá-los sempre. Alguns autores 19,21,24,25 referem o maior risco de transmissão da doença onde os hábitos de higiene não se traduzem como uma atitude usual das pessoas e defendem que a prevalência do tracoma diminui com a frequência da limpeza facial. A relação entre um rosto limpo e chances reduzidas de tracoma é uma das fortes associações encontradas na literatura 25 .…”
Section: Discussionunclassified